GROWTH AND MINRAL STATUS OF COTTON PLANTS AS AFFECTED BY ABSICISIC ACID AND SALT STRESS - Mahmoud, Safaa A.; Hussein M.M.; A.S. Taalab; Siam, Hanan S. (International Journal of Engineering Technologies and Management Research, 2019)
Application of antioxidant materials like absicisic acid to alleviate salinity stress and promote cotton growth is high effectiveness target, whereas cotton plant is an attractive industrial crop. Pot experiment was conducted to evaluate the effect of salinity stress and absicisic acid (antioxidant materials to alleviate salinity stress) on cotton growth and macro nutrients status in shoots of cotton plants. Plants subjected to two salinity levels (2500 and 5000 ppm as diluted sea water), and tap water (250ppm) as control, sprayed absicisic acid (ABA) with two concentrations (20 and 40 ppm of ABA) and distilled water as a control. Salinity decreased stem and leaves dry weight compare to the control treatment. The lower concentrations of ABA (20 and 40 ppm as a foliar spray) improve dry weight of stem and leaves. Reversely, leaves/stem ratio decreased with both concentrations of the absicisic acid. The increment in dry weight of leaves and stem or their sum showed its higher values by application 40 ppm from ABA under the 5000 ppm salinity level and also under fresh water treatment but under the 2500 ppm treatment the highest values were by 20 ppm of growth regulator. Nevertheless, L/S ratio decreased by ABA treatment, whereas, the high concentration of ABA (40ppm) was super than lower concentration (20ppm) under both salinity levels. Generally, it can be used diluted seawater in irrigation of cotton plant with spraying abscisic acid to alleviate the harmful effect of salinity.